NtNAC053, A Novel NAC Transcription Factor, Confers Drought and Salt Tolerances in Tobacco - Li, Xiaoxu; Wang, Qi; Guo, Cun; Sun, Jinhao; Li, Zhiyuan; Wang, Yaofu; Yang, Aiguo; Pu, Wenxuan; Guo, Yongfeng; Gao, Junping; Wen, Liuying (Frontiers in Plant Science, 2022)
The NAC (NAM, ATAF1/2, and CUC2) family acts as one of the largest families of transcription factor in plant kingdom and was revealed to function as the important regulators in various environmental stresses. However, few studies were reported about the biofunctions of NAC transcription factor in tobacco. In current study, we characterized a novel NAC transcription factor encoding gene NtNAC053 in tobacco, which was significantly up-regulated when exposed under the salt and drought treatments. The results of cis-acting elements analysis suggested the promoter region of NtNAC053 gene possesses number of stress responsive elements, and this gene could be induced by exogenous abscisic acid (ABA) treatment. Moreover, the NtNAC053-GFP fusion protein was localized in the cell nucleus and possessed a transactivation domain in its c-terminal, implying that NtNAC053 may undertake as a transcriptional activator in tobacco. Notably, the overexpression of NtNAC053 in tobacco resulted in hypersensitivity to ABA treatment. Furthermore, these overexpression lines showed significantly enhanced the tolerances to drought and salt stresses. Under salt and drought stresses, these overexpression lines possessed higher superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) activities. Interestingly, the expressions of putative stress-related genes, including NtCOR15A, NtRAB18, NtDREB1A, NtERF5, NtKAT2, and NtERD11, were up-regulated in these overexpression lines when subjected to salt and drought stresses. The clues provided in our study suggested that the NtNAC053 gene encode a novel NAC transcription factor and could confer the drought and salt stress tolerances by inspiring the downstream stress responsive genes and antioxidant system in tobacco.